Amelioration of Ultisol Acidity Using Coal Ash and Lignite-Enriched Compost - Fadil Fajarindo; Suwardi; Iskandar; Atfritedy Limin; Shiamita Kusuma Dewi (Department of Soil, Faculty of Agriculture, Lambung Mangkurat University, 2026)
Prolonged use of Ultisols can degrade soil quality, notably by increasing acidity. To address this, proper management practices such as adding lime, compost, coal ash, and lignite are essential. This study evaluated the ability of coal ash and lignite-enriched compost to reduce Ultisol’s acidity. A split-plot experiment was conducted with main treatments including compost (K), compost combined with FABA (Fly and bottom ash) (KF), and compost with FABA plus lignite (KFL), all at a rate of 50 tons per hectare. Sub-plot involved different application methods: broadcasting and banding (in crop rows). Results indicated that banded application of KFL raised soil pH to 5.50. Additionally, banded application significantly enhanced cation exchange capacity (CEC) and base saturation (BS) by 11.94 me 100 g⁻¹ and 45.51%, respectively, while decreasing exchangeable Al by 0.208 me 100 g⁻¹ compared to broadcasting.